(untitled) (Global Journal of Human-Social Science, 2012)
This paper has attempted to compare some macro indicators of Vietnamese economy such as supply size, demand size, incremental capital -output ratio, (ICOR), total factor productivity (TFP), saving, output multipliers and import multipliers between two stages 2000-2005 and 2006-2010.